Hepatitis B vaccine uptake and associated factors among pregnant women attending antenatal care at Gulu Regional Referral Hospital, Northern Uganda - Linda Mercy Akello; Jimmy Osuret; Jovan Galiwango; Amos Deogratius Mwaka; Christopher Garimoi Orach (PLoS ONE, 2026)
Background Hepatitis B virus (HBV) infection is a global public health concern. Uganda has a high prevalence of HBV infection among pregnant mothers. This study aimed to determine HBV vaccine uptake and associated factors among pregnant women attending Antenatal Care (ANC) at Gulu Regional Referral Hospital (GRRH). Methods This was a cross-sectional study. Data were collected from 430 participants who were selected by systematic sampling. Data were collected using an electronic questionnaire built on the Kobo Collect server and analyzed using STATA version 16.0. Prevalence ratios (PR) were calculated using a modified Poisson regression analysis to determine the association between HBV vaccine uptake and the predictors. Results More than half (53%:229/430) of the pregnant mothers had received at least a dose of the HBV vaccine. Factors statistically significantly associated with HBV vaccine uptake included age (APR = 1.10, 95% CI: 1.02–1.18), knowledge about HBV (APR = 1.06, 95% CI: 1.01–1.10), and healthcare worker communication (APR = 1.17, 95% CI: 1.04–1.32). Conclusion More than half of pregnant mothers had received at least a dose of the HBV vaccination. Age, knowledge, and healthcare communication influenced vaccine uptake. There is a need to provide adequate health education regarding the importance of completing the HBV vaccine to pregnant women and community members to improve vaccine outcomes.